“You sure there's nothing more to say?”: Indonesian Youth Culture Represented in YouTube Video Advertisements - Bobi Guntarto; Nurina Sevrina (Soegijapranata Catholic University, 2019)
Local identity, to some extent, has been influenced by globalization, mainly through the new media. As a form of digital media, YouTube video advertisements play a crucial part in promoting global products to the locals. In Indonesia, the majority of YouTube visitors are young people; thus, young people have become the main targets of the advertisements. The video advertisements may contain representation, values or references of youth culture, which are critical for young people in building their identity. This paper sets forth to explore Indonesian YouTube advertisements of LINE, an instant messaging (IM) application developed by Naver Korean company. The authors examine LINE YouTube video advertisements using textual analysis, in order to learn the portrayal of Indonesian youth culture on the videos. Digital media, bahasa gaul, and traditional or dominant cultures, as well as social connectivity, are essential for Indonesian youths in shaping youth culture and their identity. The title of this paper “You sure there’s nothing more to say?” is taken from one of the dialogues in the videos, which implies that youth culture and identity portrayed in the advertisements appreciate face-to-face social communication of young people more than individualization. It is also argued that if used aptly, YouTube video advertisements could contribute effectively to preserving local identity as a strategy of glocalization; thus, not all advertisements of global corporations may threat local identity.